The importance of viral marketing in managing communication in sport - Kowalski, Sławomir (Journal of Education, Health and Sport, 2022)
Communication management in sports organizations requires not only the use of formal tools, such as an official website, fan page or official TV channel. Effective communication should also be based on informal methods, in which the main role is played by interactions between the sports organization and its stakeholders. One such form is viral marketing, which involves sharing files with humorous, social or image content on social networks, messengers, blogs and e-mail. In the case of such forms, due to the wide range and speed of spreading opinions, especially negative ones, about the company, its services or products, it becomes necessary to control the emerging opinions. Management of information with a viral potential allows you to reach stakeholders in an informal way, influencing the building of a positive image, response in crisis situations or creating communities. The purpose of this paper is to analyze the degree of viral marketing use in sports clubs. The research was conducted in October 2021 on different social media. However, due to the extensive scope of the research, this paper focuses on the social network Facebook. The research is concerned with determining the use of viral marketing potential in information management and identifying the characteristics of this form of influencing stakeholders. Due to the limited volume of the article, the main subject of the study is the Polish clubs of the highest level of competition against the background of examples from abroad. The main hypothesis of this article assumes that Polish clubs do not fully use the viral potential and communication activities are based on official messages. Communication management is based on peer benchmarking and replication of what others are doing. It is also assumed that departments responsible for communication in sports clubs do not fully use foreign models.